Examining Green Human Resource Management Practices and Their Impact on Innovative Culture - Dwipayani, Ni Gusti Ayu Kadek Eva; Darma, Gede Sri (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
This research tries to examine the practice of GHRM, the factors that support and hinder its implementation, its impact on the company’s innovative culture and the benefits it provides to the company itself. This research employs a mixed-methods approach, combining qualitative and quantitative data collection and analysis to provide a comprehensive understanding of GHRM practices and their effects. Qualitative data were collected through semi-structured interviews with 10 informants selected based on purposive sampling criteria. The qualitative data were analyzed using NVivo R1 software to identify key themes and patterns. Quantitative data were gathered via a structured questionnaire distributed to 50 respondents, who were selected using a purposive sampling technique. This questionnaire utilized a Likert scale to measure perceptions of GHRM practices and their relationship with innovative culture. The quantitative data were analyzed using Structural Equation Modeling (SEM) to assess the relationships between GHRM practices and innovative culture. The results of this study indicate that GHRM practices have been implemented at the hotel and also GHRM has had a positive impact on innovative culture, where the innovative culture instilled through GHRM creates an environment where employees are encouraged to think creatively, find new solutions, and support environmental sustainability. While the hypothesis results state that there is a significant positive effect of GHRM on Innovative culture.